The role of inflammation in hematopoiesis and bone marrow failure: What can we learn from mouse models? - Wang, Jun; Erlacher, Miriam; Fernandez-Orth, Juncal (Frontiers in Immunology, 2022)
Hematopoiesis is a remarkable system that plays an important role in not only immune cell function, but also in nutrient transport, hemostasis and wound healing among other functions. Under inflammatory conditions, steady-state hematopoiesis switches to emergency myelopoiesis to give rise to the effector cell types necessary to fight the acute insult. Sustained or aberrant exposure to inflammatory signals has detrimental effects on the hematopoietic system, leading to increased proliferation, DNA damage, different forms of cell death (i.e., apoptosis, pyroptosis and necroptosis) and bone marrow microenvironment modifications. Together, all these changes can cause premature loss of hematopoiesis function. Especially in individuals with inherited bone marrow failure syndromes or immune-mediated aplastic anemia, chronic inflammatory signals may thus aggravate cytopenias and accelerate disease progression. However, the understanding of the inflammation roles in bone marrow failure remains limited. In this review, we summarize the different mechanisms found in mouse models regarding to inflammatory bone marrow failure and discuss implications for future research and clinical practice.